(3eONd Gdi GdEMUGA GdhUaj s - (3djfOI (B, (3MQGhHjIs ((3GdLRGFQ (B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2017)
(3JfGhd GdcGJH ehVhY GdGMUGA GdhUaj MjK JMOK ef NdGd aUhd OQGSJg Yf GdeaGgje GdCSGSjI aj GdGMUGA GdhUaj hYf ebGjjS GdfRYI GdeQcRjI GdhSW GdMSGHj , HGdGVGaI Gdi ebGjjS GdJTJJ hebGjjS GdehVY(B.s
(3GdeQGLY U(B.95s
Keywords: (3GdEMUGA GdhUajs